Analisis Strategi Pengembangan Usaha Kopi Arabika Di Masa Pandemi COVID - 19 (Studi Kasus Kopi Gayo Atulintang) - marahadi marahadi; Irawan Irawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study was to analyze the development of the Arabica coffee business in Atulintang Village, Takengon Regency. The approach taken is a direct action plan where the analysis is carried out comprehensively. The results of this study show that the development of the Gayo coffee business in Atu Lintang Village has complex problems due to the Covid-19 pandemic. The results of the calculation of the income of Gayo coffee farmers are very concerning where the expected profit expectations are not in line with their expectations. Even coffee farmers find it difficult to sell their crops, plus the selling price continues to decline. This is due to the unstable price of Gayo coffee plus the price will drop during the current Covid-19 pandemic. For this reason, it is necessary to develop a more productive business development strategy in order to maximize farmer profits. The right SWOT strategy for Atu Lintang Village Farmers in developing their business and facing competition between other Gayo coffee businesses is a market penetration strategy that emerges from the QSPM matrix.